PyCCAPT: A Python Package for Open‐Source Atom Probe Instrument Control and Data Calibration - Monajem, Mehrpad; Ott, Benedict; Heimerl, Jonas; Meier, Stefan; Hommelhoff, Peter; Felfer, Peter (Microscopy research and technique, 2025)
ABSTRACT Currently, the vast majority of atom probe instruments in use are commercial systems with closed, proprietary software. This is limiting for many experiments where low‐level access to machine control, experiment data, or custom instrument setups is necessary. Over the past decade, advancements in off‐the‐shelf detector systems, fast data bus systems, and the availability of high‐level programming languages such as Python have made it feasible to design and construct atom probe systems without extensive engineering expertise. Despite this progress, developing control system software, associated instruments, and data calibration algorithms remains a significant challenge for many projects. In this article, we introduce an atom probe control system that can be flexibly adapted to various hardware configurations. This system also includes essential instrument and experiment calibration algorithms, offering complete transparency to the user. This framework provides flexibility for innovative experiments and enhances calibration accuracy not possible with commercial systems. The methods and algorithms discussed are implemented in Python Control and Calibration for Atom Probe Tomography (PyCCAPT), which is an open‐source solution for APT, addressing a gap in experimental control and data processing. While not compatible with commercial atom probes for data acquisition, its calibration module can be used for direct‐flight‐path systems and adapted for reflection‐based instruments. Open‐source PyCCAPT software enables flexible atom probe control and calibration, offering transparency and adaptability for diverse hardware setups. By integrating advanced algorithms, it enhances experiment precision and supports innovative research beyond the limitations of proprietary systems. Open‐source PyCCAPT software enables flexible atom probe control and calibration, offering transparency and adaptability for diverse hardware setups. By integrating advanced algorithms, it enhances experiment precision and supports innovative research beyond the limitations of proprietary systems.